Modelling functional resilience of microbial ecosystems: Analysis of governing processes. (March 2017) - König, Sara; Worrich, Anja; Centler, Florian; Wick, Lukas Y.; Miltner, Anja; Kästner, Matthias; Thullner, Martin; Frank, Karin; Banitz, Thomas
Abstract: Functional stability of microbial ecosystems subjected to disturbances is essential for maintaining microbial ecosystem services such as the biodegradation of organic contaminants in terrestrial environments. Functional responses to disturbances are thus an important aspect which is, however, not well understood yet. Here, we present a microbial simulation model to investigate key processes for the recovery of biodegradation. We simulated single disturbances with different spatiotemporal characteristics and monitored subsequent recovery of the biodegradation dynamics. After less intense disturbance events local regrowth governs biodegradation recovery. After highly intense disturbance events the disturbance pattern's spatial configuration is decisive and processes governing local functional recovery vary depending on habitat location with respect to the spatial disturbance pattern. Local regrowth may be unimportant when bacterial dispersal from undisturbed habitats is high. Hence, our results suggest that spatial dynamics are crucial for the robust delivery of the ecosystem service biodegradation under disturbances in terrestrial environments. Highlights: We present a generic simulation model of microbial degradation after disturbances. Recovery processes were disentangled by a spatially resolved mechanistic analysis. Decisive processes for local functional recovery vary for different locations. Overall functional resilience depends on the spatial pattern of the disturbance.